Katzu
contestada

Please help ASAP! Will give BRAINLIEST! Please read the question THEN answer correctly! No guessing.

Please help ASAP Will give BRAINLIEST Please read the question THEN answer correctly No guessing class=

Respuesta :

Annder

Answer:

A, B

Step-by-step explanation:

(x+6)(x-3)

x = -6, 3

Answer:A and B

Step-by-step explanation:

x^2+3x-18=0

The two numbers which their product is -18 and their sum is 3 are +6 and -3

Therefore we remove 3x from the equation and replace with +6x-3x

x^2+6x-3x-18=0

We Factorise

x(x+6)-3(x+6)=0

Factorise again

(x+6)(x-3)=0

Equate (x+6) and (x-3) to be equal to zero separately

x+6=0 or x-3=0

x=-6 or x=3

ACCESS MORE